PERANAN KOMUNITAS BERBUDAYA TORAJA SEBAGAI PENYANGGA KEDATUAN LUWU - M. Nur (BRIN, 2006)
In local historiography, Luwu is one of the kingdoms that has received considerable attention compared to other kingdoms. If we have to conclude some of the readings about Kedatuan Luwu, the correct sentence is that the Kingdom of Luwu is a kingdom that deserves to be reckoned with in the historiography of the archipelago, at least in the 14th century, predating the kingdom of Gowa on the west coast of South Sulawesi. Even though we have arrived at this conclusion without ever having been significantly rebutted, this does not mean that the perspective that has been used to observe Luwu has no weaknesses.